Functional and structural characterization of four mouse monoclonal antibodies to complement C3 with potential therapeutic and diagnostic applications. Issue 3 (6th February 2017) - Subías Hidalgo, Marta; Yébenes, Hugo; Rodríguez‐Gallego, César; Martín‐Ambrosio, Adrián; Domínguez, Mercedes; Tortajada, Agustin; Rodríguez de Córdoba, Santiago; Llorca, Oscar
Abstract : By immunizing C3‐deficient mice with a mixture of human C3b, iC3b, and C3dg fragments, we generated novel mAbs that target functionally relevant regions or neo epitopes. The structural characterization of these mAbs and the analysis of the consequences of the binding to their targets illustrate important therapeutic and diagnostic potentialities. Abstract : C3 is the central component of the complement system. Upon activation, C3 sequentially generates various proteolytic fragments, C3a, C3b, iC3b, C3dg, each of them exposing novel surfaces, which are sites of interaction with other proteins. C3 and its fragments are therapeutic targets and markers of complement activation. We report the structural and functional characterization of four monoclonal antibodies (mAbs) generated by immunizing C3‐deficient mice with a mixture of human C3b, iC3b and C3dg fragments, and discuss their potential applications. This collection includes three mAbs interacting with native C3 and inhibiting AP complement activation; two of them by blocking the cleavage of C3 by the AP C3‐converase and one by impeding formation of the AP C3‐convertase. The interaction sites of these mAbs in the target molecules were determined by resolving the structures of Fab fragments bound to C3b and/or iC3b using electron microscopy. A fourth mAb specifically recognizes the iC3b, C3dg, and C3d fragments. It binds to an evolutionary‐conserved neoepitope generated after C3b cleavage by FI, detecting iC3b/C3dg deposition over opsonized surfaces by flow cytometry and immunohistochemistry in human and other species. Because well‐characterized anti‐complement mAbs are uncommon, the mAbs reported here may offer interesting therapeutic and diagnostic opportunities.